2017
DOI: 10.1021/acsami.7b00272
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin-Derived Graphene–Silicate Hybrid Materials Are Biocompatible and Synergistically Promote BMP9-Induced Osteogenic Differentiation of Mesenchymal Stem Cells

Abstract: Graphene-based materials are used in many fields but have found only limited applications in biomedicine, including bone tissue engineering. Here, we demonstrate that novel hybrid materials consisting of gelatin-derived graphene and silicate nanosheets of Laponite (GL) are biocompatible and promote osteogenic differentiation of mesenchymal stem cells (MSCs). Homogeneous cell attachment, long-term proliferation, and osteogenic differentiation of MSCs on a GL-scaffold were confirmed using optical microscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Total RNA was isolated using TRIzol Reagents (Invitrogen, Carlsbad, CA, USA) as described. 54 , 55 , 56 The cDNA synthesis was carried out using hexamer and M-MuLV Reverse Transcriptase (New England Biolabs, Ipswich, MA, USA). The cDNA products were diluted 10- to 50-fold and used as PCR templates.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated using TRIzol Reagents (Invitrogen, Carlsbad, CA, USA) as described. 54 , 55 , 56 The cDNA synthesis was carried out using hexamer and M-MuLV Reverse Transcriptase (New England Biolabs, Ipswich, MA, USA). The cDNA products were diluted 10- to 50-fold and used as PCR templates.…”
Section: Methodsmentioning
confidence: 99%
“…The image data were quantitatively analyzed by Amira 5.6 (Visage Imaging, Inc.), and 3-D volumetric data and bone density were determined as previously described. 84 87 …”
Section: Methodsmentioning
confidence: 99%
“…57 Polymers include poly(L-lactide) (PLLA), 46 poly(dopamine) (PDA), 68 poly(ɛ-caprolactone) (PCL), 14,36,203 poly(ethylenimine) (PEI), 37, 82 poly(lacticcoglycolic acid) (PLGA)-tussah, 61 silk fibroin (SF), 43 polyethylene terephthalate-based artificial ligament group (PET-ALs), 78 47,65,89 and inductively coupled plasma-optical emission spectroscopy (ICP-OES) 49,71 were employed to measure the release rate of ions, and inductively coupled plasma-mass spectroscopy (ICP-MS) 64 was utilized to assess the Ca/P ratio. Additional assays and measures used for sample characterization include thermal gravimetric analysis (TGA), 37,71,82,84,87 energy dispersive X-ray spectroscopy (EDX), 33 75 swelling study, 75 weight loss measurement, 60 diametral tensile strength (DTS), 60 nanoindentation measurements, 67, 76 photoluminescence (PL) spectra, 94 elemental analysis experiment, 25 magnetometry, 25 selected-area electron diffraction (SAED), 57, 91 wettability evaluation, 89 roughness evaluation 14,28,89 and PL spectrum. 94…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The -NH2 and C=O functional groups of Ct were reported to contribute to bio-mineralization. 48 Zou et al 87 demonstrated that Gn-derived graphene/laponite (GL) powder enhanced osteodifferentiation due to the physical stresses induced on cells, as a result of the surface topographic, stiffness and roughness of graphene sheet .87 Furthermore, the GL-powder promoted matrix mineralization of the cells by increasing BMP9-induced osteogenesis; BMP9 is one of the most potent to induce MSC osteogenic differentiation.…”
Section: Graphene and Polymersmentioning
confidence: 99%
See 1 more Smart Citation